Konstruksi Narasi Politik Generasi Z di Tiktok: Studi Praktik Komunikasi Digital Pemilih Muda Pasca Pemilu 2024 - Levi Mubarok (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The transformation of Indonesia's political communication landscape post-2024 elections demonstrates significant phenomena regarding Generation Z's involvement in constructing political narratives through the TikTok platform. Generation Z, representing 60 percent of Indonesian voters, has changed the paradigm of political participation by utilizing social media as a strategic arena for shaping political discourse. This research aims to analyze the process of Generation Z's political narrative construction on TikTok post-2024 elections, explore digital communication practices in producing, distributing, and consuming political content, and understand the mechanisms of political identity negotiation through platform features and participatory culture. The research employs a qualitative approach with a library research method analyzing reputable academic literature from 2020-2025 through qualitative content analysis techniques with stages of data reduction, data presentation, and conclusion drawing. Research findings reveal that Generation Z's political narrative construction is characterized by the use of inclusive language styles, creative visual-multimodal elements, and content orientation that shifts from electoral campaigns toward critical evaluation and deliberative participation. Digital communication practices include authentic visual-based content production, distribution through platform algorithmic logic, and consumption with critical interpretation influenced by media literacy. Political identity negotiation occurs in digital liminality spaces through the utilization of interactive features such as duets, stitches, and hashtag challenges, while facing challenges of disinformation, discourse polarization, and algorithmic bias. The research recommends developing comprehensive digital political literacy programs, adopting authentic communication strategies by political actors, increasing platform algorithmic transparency, and conducting further research to explore the long-term dynamics of digital political narrative construction and its impact on the quality of Indonesia's deliberative democracy